1991
DOI: 10.1111/j.1365-2222.1991.tb00803.x
|View full text |Cite
|
Sign up to set email alerts
|

Pigeon breeders' lung—the effect of loft litter materials on airborne particles and antigens

Abstract: An Andersen sampler was used to collect different sized fractions of airborne dust within pigeon lofts. Antigens associated with pigeon breeders' lung were then measured using an ELISA technique. Levels of soluble antigen in the 0.5-5 microns range correlated significantly with airborne particle concentrations in the same range, determined by particle size analysis. However, antigenic material was not soley confined to the 0.5-5 microns fraction and was detected in particles up to 11 microns in diameter. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Some fanciers find it helpful to increase the level of ventilation in their loft, but Edwards et al showed that this did not reduce particle and antigen counts in the loft, possibly because air turbulence generates as many airborne particles as are eliminated to the outside by ventilation. 13 Although there is often an apparent beneficial response to corticosteroids, it is difficult to distinguish between the effects of treatment, the natural course of the disease, and the effect of antigen avoidance. There have been no controlled trials of corticosteroids in patients with pigeon fancier's lung, but studies of patients with farmer's lung provide insight into their effects on extrinsic allergic alveolitis.…”
Section: Pigeon Fancier's Lungmentioning
confidence: 99%
See 1 more Smart Citation
“…Some fanciers find it helpful to increase the level of ventilation in their loft, but Edwards et al showed that this did not reduce particle and antigen counts in the loft, possibly because air turbulence generates as many airborne particles as are eliminated to the outside by ventilation. 13 Although there is often an apparent beneficial response to corticosteroids, it is difficult to distinguish between the effects of treatment, the natural course of the disease, and the effect of antigen avoidance. There have been no controlled trials of corticosteroids in patients with pigeon fancier's lung, but studies of patients with farmer's lung provide insight into their effects on extrinsic allergic alveolitis.…”
Section: Pigeon Fancier's Lungmentioning
confidence: 99%
“…12 In patients with left ventricular dysfunction after myocardial infarction, angiotensin converting enzyme inhibitors reduced the risk of all cause mortality by 19%, the risk of non-fatal and fatal vascular events by 21%, and the development of severe heart failure by 37% over 42 months of follow up. 13 In patients with clinical evidence of heart failure after myocardial infarction, treatment with an angiotensin converting enzyme inhibitor over 15 months resulted in a significant 27% reduction in risk of death and a 19% reduction in vascular events. 14 The Scandinavian simvastatin survival study of patients with angina or a history of myocardial infarction clearly showed, in patients with a total cholesterol concentration of 5.5-8.0 mmol/l, a 30% reduction in total mortality and a 42% reduction in coronary mortality over a five year follow up.…”
mentioning
confidence: 99%
“…sepiolite, but lower num bers with others, e.g. woodchip, compared with PD not voided onto litter agents [36]. The effect of PD litter inter actions on respirable particle and airbone allergen burden is shown in table 3.…”
Section: Humidifier Fevercaused By Inhaling Allergens From Contaminatmentioning
confidence: 99%
“…dehydrating agent upon which the voided PD falls [36]. The situation is complicated by the interaction between PD and some litters, producing large numbers of small (micrometre sized) particles with some, e.g.…”
Section: Humidifier Fevercaused By Inhaling Allergens From Contaminatmentioning
confidence: 99%
See 1 more Smart Citation